PENGEMBANGAN POTENSI KARANG TARUNA MELALUI KEMANDIRIAN WIRAUSAHA BERBASIS POTENSI LOKAL DI KABUPATEN GRESIK - Moh. Agung Surianto; Rahmat Agus Santoso (Institute of Research and Community Outreach - Petra Christian University, 2015)
Gresik as one of the 38 districts and cities in East Java has the complexity of the problems of youth development, especially the number of unemployment. The subject for this community service program covers Karang Taruna Glanggang and karang Taruna Gadukan in the area of Gresik Regency. The youth has positive motivation in joining organization and became important point to create the youth to have ability to be an entrepreneur by local potention from the local village. Several programs were implemented in the form of enhancing youth entre¬preneur mindset, training of fish processing, marketing and financial administration also consultancy program. The outcome of this program;a. The emerging of start-up business b. PIRT licensing in Gresik District Health Office for processed fish products.